An Analysis of Communication System and Stakeholder Mapping in Supporting the National Shrimp Pond Production Acceleration Program 2024 - Siahaan, Flora Meliana; Anggraini, Katry; Amalliah, Amalliah (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
This research was conducted from observation (observation) and literature. The author collects various information from national and international journals, news in the media, articles, e-books, modules, diktats, and other research results related to the topic of discussion, namely the communication system and stakeholder mapping (stakeholders), then analyses in depth to be able to answer the formulation of the problem raised in this paper. Support or involvement of stakeholders in accelerating the 2024 national shrimp production program is needed, there is no stakeholder support, so the acceleration of achieving production targets will not be implemented. The stakeholders and actors detected to have a role in this program are central and regional governments, the Ministry of Marine Affairs and Fisheries, banks or investors, private companies, non-governmental organizations (NGOs), farmers, and surrounding communities.